PERSEPSI GURU TERHADAP PELAKSANAAN GERAKAN LITERASI DI SELOLAH DASAR NEGERI 110 PEKANBARU - Putri Zulhaini Adawiyah; M. Jaya Adiputra; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to determine how teachers' perceptions of the implementation of the literacy movement in 110 Pekanbaru Elementary Schools and differences of opinion based on functional factors that influence it. This research is a descriptive quantitative study in which the population and sample are 25 elementary school teachers and principals at Pekanbaru 110 Public Schools. The data collection method used was a questionnaire. Data collection techniques consist of three stages: questionnaire, documentation, and interview. The data analysis technique used is descriptive statistics by calculating the percentage of teacher perceptions on each indicator. The overall recapitulation of research results is classified as good. This can be seen from the results of the percentage of teacher perceptions based on indicators on the questionnaire namely strengthening the capacity of facilitators 80.6%, increasing the number and variety of quality reading sources 85.8%, expanding access to learning resources and 79.8% coverage of learning participants, increasing public involvement 82.6%, governance strengthening 77.6%, habituation stage 74.2%, development stage 76.8%, and learning stage 79.2%, and there are differences in teacher perceptions based on functional factors that influence it.Key Words: Teacher Perceptions, School Literacy Movements.